2020
DOI: 10.3144/expresspolymlett.2020.40
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic mechanical characterization of cross-linked polyethylene foams: The effect of density

Abstract: We performed the complex static and dynamic mechanical characterization of cross-linked polyethylene foams; we investigated the effect of foam density on various mechanical properties and the relationship between cell structure and mechanical behavior. The impact damping and energy absorption properties of the foams were determined by falling weight impact tests, while static mechanical properties were determined by compression and compression set tests. The experimental results validated our hypothesis that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
9
2
Order By: Relevance
“…The results showed a linear relationship between relative density and impact strength. In contrast, our previous study 27 on cross‐linked polyethylene foams showed that the relationship between foam density and mechanical properties could be described by the power law. Marsavina et al 28 also showed that mechanical properties are primarily influenced by the density of the foam, which has a more significant effect than the direction of the load.…”
Section: Introductioncontrasting
confidence: 72%
“…The results showed a linear relationship between relative density and impact strength. In contrast, our previous study 27 on cross‐linked polyethylene foams showed that the relationship between foam density and mechanical properties could be described by the power law. Marsavina et al 28 also showed that mechanical properties are primarily influenced by the density of the foam, which has a more significant effect than the direction of the load.…”
Section: Introductioncontrasting
confidence: 72%
“… 63 According to the data obtained at 90 °C, the samples showed around 90% of compression set, but at 80 °C, it was about 80%. Kmetty and coworkers conducted the compression set for cross-linked polyethylene foams, and their results exhibited 95% compression set after 24 h. 64 Furthermore, Park and Kim 65 prepared the ethylene vinyl acetate copolymer (EVA)/multiwalled carbon nanotube (MWCNT) nanocomposite foams and these foams showed around 55% of compression set value at 50 °C. In the present study, the maximum compression set value obtained for cassava starch-based foam is 73.86% and the value is comparatively better than previously reported data for TDI, cross-linked polyethylene, and EVA/MWCNT nanocomposite foams.…”
Section: Resultsmentioning
confidence: 99%
“…According to the data obtained at 90 °C, the samples showed around 90% of compression set, but at 80 °C, it was about 80%. Kmetty and coworkers conducted the compression set for cross-linked polyethylene foams, and their results exhibited 95% compression set after 24 h . Furthermore, Park and Kim prepared the ethylene vinyl acetate copolymer (EVA)/multiwalled carbon nanotube (MWCNT) nanocomposite foams and these foams showed around 55% of compression set value at 50 °C.…”
Section: Resultsmentioning
confidence: 99%
“…These foams are extensively used by the vehicle industry, the building industry, the packaging industry, and they can be found in a lot of sports equipment. This results that the volume of the global foam market reached 113 billion dollars in 2019, and the yearly increase is about 4% 1–5 …”
Section: Introductionmentioning
confidence: 99%